Assessment of groundwater vulnerability and sensitivity to pollution in Aquifers Zanjan Plain, Iran - P.M.S. Abad; E Pazira; M.H.M. Abadi; P.A. Nejad (Journal of Applied Sciences and Environmental Management, 2018)
Groundwater pollution caused by human activity is a serious environmental problem in cities. Pollution vulnerability assessment of groundwater resources provides information on how to protect areas vulnerable to pollution. The present study is a detailed investigation of the potential for groundwater contamination through construction of a vulnerability map for the study aquifer in Zanjan plain. The parameters used in the DRASTIC model are depth-to-water table, net recharge, aquifer media, soil media, topography, impact of vadose zone, and hydraulic conductivity. The overlying index, GIS and AHP were used with the modified DRASTIC model to evaluate the vulnerability of the alluvial Zanjan aquifer to nitrates. AHP was used to determine the rate coefficient of each parameter. The correlation coefficients were produced by comparing the vulnerability index with the nitrate concentrations in the groundwater. The results show that the DRASTIC index values for the study area ranged from 82 to 186 and were divided into low, medium, and high vulnerability classes. GIS was found to provide an efficient environment for such analyses. The DRASTIC aquifer vulnerability map indicates the dominance of the medium vulnerability class in the most parts of the study area (49.033%). The high correlation coefficient for the modified DRASTIC index (0.92) and nitrate layer than for the standard DRASTIC model (0.74) suggests that the actual condition in the study area can be better explained by the modified DRASTIC model.